Case Report: Unusual radiological findings in adult human metapneumovirus infection - Jiun, Ling Chieng; Yee, Ho Shuang; Azmi, Mohd Imree (Frontiers in Medicine, 2025)
Human metapneumovirus (hMPV) is a globally prevalent respiratory pathogen, primarily affecting young children, the elderly, and immunocompromised individuals. Typical airway-centric radiological findings like other viral infections are commonly reported. However, atypical findings in computed tomography (CT) have yet to be reported in literature. We present a case of hMPV infection in an immunocompetent adult with rare findings of cystic lesions in CT thorax. A 67-year-old female with underlying valvular heart disease and chronic heart failure presented to our centre with respiratory symptoms and reduced effort tolerance. Initial chest radiographs were suggestive of an active pulmonary infection superimposed on acute pulmonary edema, leading to empirical antibiotic treatment with the differentials of community-acquired pneumonia. Despite antibiotics and diuretics treatment, her condition worsened requiring oxygenation supplementation. High-resolution computed tomography (HRCT) thorax was performed and demonstrated typical airway-centered findings including peribronchial wall thickening and ground-glass opacities. In addition, multiple cystic lung lesions of varying sizes in random distribution are seen scattered in both lung fields. Reverse transcription polymerase chain reaction (RT-PCR) confirmed an hMPV infection, with no evidence of bacterial or other viral co-infection. The patient improved with supportive care and was discharged after 5 days of admission. While there is no preceding literature on atypical lung changes during the course of hMPV infection, this case highlights the possibility of the broader imaging dynamics of this virus.